PENGARUH SOSIAL EKONOMI ORANG TUA DAN KARAKTERISTIK INDIVIDU TERHADAP HASIL BELAJAR SISWA KELAS XI DI SMA NEGERI 1 KOTA JAMBI - Cahyati, Sri Fuji Rahayu; Mayasari, Mayasari (SJEE (Scientific Journals of Economic Education), 2021)
AbstractThis study aims to determine 1) The socio-economic description of parents, individual characteristics and learning outcomes. 2) The influence of parents' socioeconomic and learning outcomes. 3) the influence of individual characteristics on learning outcomes. 4) The influence of parents' socioeconomic and individual characteristics simultaneously on student learning outcomes. This research design uses quantitative research methods, with data collection techniques through observation, interviews, and questionnaires. Where the population in this study were 143 students with a sample of 105 students. The research instrument test technique used in this study is the Validity and Reliability Test, while the classical assumption test used is the Linearity Test, Multicollinearity Test, Normality Test, Homogeneity Test, and Multiple Regression Test. The results showed that: 1) The socio-economic of parents was included in the poor category with an average TCR value (X1) of 50.60%, (X2) 70.11%, and the students' learning outcomes in economics subjects with a value of less than 68 as many as 71 students while those who scored above 68 were 34 students. 2) There is a socio-economic influence of parents on learning outcomes which can be seen from the value of tcount > ttable of parents' socioeconomic variables of 3.158 > 1.658. 3) There is an influence of individual characteristics on learning outcomes that can be seen from the value of tcount > ttable, namely 4.461 > 1.658. 4) There is a simultaneous influence of parents' socioeconomic and individual characteristics on learning outcomes as indicated by the value of Fcount > Ftable of 16.475 > 3.04. Socio-economic parents affect the development of children's learning in the facilities and means of learning at home and at school. In addition to fulfilling the character building facilities, it also aims to improve better study habits, as well as the spirit of learning in students. Indirectly socio-economic conditions have an impact on students' self-change in order to get better learning outcomes than before.Keywords: Socio-Economic, Characteristics, Learning Outcomes.